INTERNALISASI PENDIDIKAN ANTIKORUPSI BERBASIS KOMUNITAS “PASRAMAN WIDYA SARASWATI” - Dewi Ambarwati; Khilda Nafisatus Zahro; Ummi Khusnul Chotimah; Putri Muflihatul Karomah (LP2M Universitas Ibrahimy, 2023)
Anti-corruption education is needed to build children's character with integrity. Children are the next generation of the nation who should have national insight and anti-corruption integrity. It cannot be denied that there are some areas that have problems related to the implementation of anti-corruption education for children. The same thing happened in Kesamben Village, Ngajum District, Malang Regency, where the village still needs teaching staff to provide the right method in teaching anti-corruption values for children. this service activity was carried out by the UNIRA Malang KKN-T team using a service learning (S-L) approach, with the ultimate goal of stimulating children to be able to map problems, find solutions and reflect on the results of activities. Based on the service activities that have been carried out, it is evident that all participants are very enthusiastic and can map problems and solutions to reflect back on the material that has been given.